Total Articular Knee Replacement Using Polyurethane - Pritchett, James W. (The Journal of Knee Surgery, 2020)
This study reviewed the early use of polyurethane for total knee resurfacing, the long-term results of polycarbonate urethane (PCU) for total knee replacement and conducted wear simulator testing of PCU. In 1959 and 1960, 10 patients underwent total articular polyurethane knee replacement (polyethylene was not available). The polyurethane was placed on the articular surface of the femur with metal surfaces on the tibia and patella. In 1996 and 1997, four patients received a newer PCU tibial insert in revision procedures; all had well-fixed prostheses, but no revision polyethylene implants were available. In addition, this study evaluated six new PCU tibial inserts in a 10-million cycle (Mc) wear simulator. All 10 of the early knees performed well clinically and 2 knees were functional for more than 30 years. Of the four more recent patients, all knees remain functional at more than 20 years' follow-up with no signs of wear or osteolysis. Wear simulator testing found mean material loss of 14.2 mg/Mc which equates to a volumetric wear of 11.9 mg/Mc, similar to the wear of conventional polyethylene. Polyurethane performs well as conventional polyethylene but not better than current cross-linked polyethylene tibial inserts. Its large wear particles (mean, 11 µm) and biocompatibility are less likely to cause an inflammatory response leading to pain and bone loss. Newer, superior polyurethanes can again be considered a candidate material for the tibial insert of a total knee replacement. A larger study may be able to validate polyurethane as an alternative material for joint replacement.
Keywords: polyurethane; knee resurfacing; knee replacement; arthroplasty; polyurethane wear